Virtual Reality in the Care of People with Dementia: A Single-Case Research Study - K. Gusdal Annelie; Gustafsson Christine (Journal of Patient Care and Services, 2020)
More than 90% of people with dementia develop behavioral and psychological symptoms of dementia. First-line care strategies in dementia care should consider a combination of pharmacological and non-pharmacological interventions. The present single-case research study aimed to evaluate the use of virtual reality in the context of behavioral and psychological symptoms of dementia, quality of life, and medication use among people with dementia. Ten persons with dementia used virtual reality for a mean of twice per week for eight weeks. In each virtual reality session, lasting for a maximum of 30 minutes, the persons with dementia chose one to three short films from 11 different films: a hen run, a farm with animals, two cafés, an old-fashioned grocery shop, a local river, a square in the local city, a museum, a castle, a fishing boat and an Austrian mountain scenery. Quantitative and qualitative data were collected pre-, during, and post-intervention. No major differences in the quantitative data in terms of behavioral and psychological symptoms of dementia, quality of life, or medication use were observed. However, the qualitative data showed that the use of virtual reality provided the persons with dementia with short-term enjoyment, heightened energy and alertness, and an experience of reminiscence. The use of virtual reality may therefore serve as a complementary tool to the existing non-pharmacological management techniques of people with dementia in nursing homes.
Keywords: Behavioral and psychological symptoms of dementia